DBE Meter for Retail Gasolator - Wahyu; Fransiskus; Prasetyo; Andri (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
The development of vehicles in demand for quantities on the highways has caused fuel consumption to increase. Thise will the Public Fuel Filling Stations (SPBU)sometimes unable to serve the public demand due to run out of fuel. This causes the people to turn to retail gasoline sellers that have minimal accuracy in the quantities they sell. Measurement of the flow of fuel entering the vehicle tank can be done by an electronic device in the form of a flowmeter and also control with Arduino Nano which can be injected by the control program. Therefore, it is made in the form of a minimalist funnel that can be carried easily by the user, besides that it can display the amount of fuel entering the vehicle’s tank. The test results show the measurement error value of 0.9% - 2.8% so that it can still be acceptable at the lawful limit.